The development of Adobe Flash media uses the guided discovery learning model for learning activities and learning outcomes in the buffer solution material - Lili Inda Sari (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The background of this research is the low student learning outcomes and the need for more activeness and motivation of students in learning chemistry. The development of guided discovery-based Flash media is crucial for supporting student learning outcomes and enhancing their understanding of chemical concepts. This study aims to determine students' and teachers' feasibility, effectiveness, and responses to the developed Flash media. Purposive sampling was used to select two classes for this research. These classes were chosen because the members were selected from the population based on the teacher's recommendation after evaluating the material covered in the sample class. The Guided Discovery model with Adobe Flash media made Class XI MIA 1 an experimental class. In contrast, the Direct Instruction learning approach made Class XI MIA 2 a control class. The results of research conducted at SMA Negeri 9 Medan can be concluded that there is an influence on student learning outcomes and activities when using Guided Discovery Based Adobe Flash media on class XI Buffer Solution material. These student activities contribute to aligned learning outcomes of 18.1 %. At the same time, 81.9% was caused by a lack of student interest in participating in teaching and learning activities, time allocation for implementation, and teacher willingness. The application of Guided Discovery learning media with Adobe Flash media can improve student learning outcomes in the experimental class compared to students taught with the Direct Instruction model